(untitled) (Bangladesh Journal of Otorhinolaryngology, 2013)
CSOM is a most common ENT disease in our country, among them the atticoantral variety is life threatening if not treated earlier. So treatment plan is still radical surgery to eradicate the disease to save life ignoring the hearing conservation. Henceforth post operative hearing loss remains a problem for the patient. Ensuring total clearance of the disease depending on the ossicular status, tragal cartilage graft was used as easily available material for ossiculoplasty to improve the post operative hearing .The study presents 35 ear operation of varied middle ear pathology using tragal cartilage & perichodrium as a choice graft. We have recorded our observation & result & concluded that tragal cartilage & perichondrium is an ideal graft for ossiculoplaty. The objective of study was to asses the efficacy of tragal cartilage, the functional capacity in restoring hearing acuity, its mechanical survival, its extrusion rate & its functional integrity in ossicular reconstruction. The patients those underwent surgery in Sir Salimullah Medical College Mitford Hospital had significant improvement of hearing with no recurrence of disease. DOI: http://dx.doi.org/10.3329/bjo.v19i1.14860 Bangladesh J Otorhinolaryngol 2013; 19(1): 24-28